Total and Sand Floodplain Deposition on an Inside Bend During the 2019 Missouri River Flood - Mansfield, Michael; John Shelley; Stanford Gibson (Midcontinent Geoscience, 2024)
Elwood Bottoms is a wildlife reserve that lies on the west side of the Missouri River, across from St. Joseph, Missouri. In 2019, the Missouri River inundated Elwood Bottoms for 73 days, much longer than the 1.85-day annual average outside of major flood events. This paper analyzes the floodplain deposition on Elwood Bottoms during the 2019 flood using repeated LiDAR, ground-based cross section surveys, and sediment sample datasets. The 2019 flood deposited 215,000 m3 of sediment on this floodplain. Sand concentrations in the deposits ranged from 8% to 100%. The authors computed a spatially varying sand fraction and used it to estimate a total sand deposition of 93,000 m3, roughly one-third the sediment volume scoured in the channel along the same reach during the flood. The computed sand deposit exceeded previous estimates for a similar long-term flood in 2011 by a factor of 3.5, which might stem from better computational methods or might reflect actual differences in the depositional behavior of the events. Floodplain deposits generally thinned and fined with distance from the channel, and subsurface samples were coarser than surface samples. The surficial 90th percentile of grain size distribution (d90) decreased by an order of magnitude across the deposits, from approximately 0.1 mm close to the channel to 0.01 mm at the distal edge of the inundated floodplain.